Hydrothermal liquefaction of Ulva prolifera macroalgae and the influence of base catalysts on products. (November 2019) - Yan, Long; Wang, Yufei; Li, Jian; Zhang, Yu; Ma, Langlang; Fu, Feng; Chen, Bi; Liu, Huijin
Highlights: Base catalytic hydrothermal liquefaction of U. prolifera was studied. Maximum bio-oil was obtained (26.7 wt%) with KOH (0.1 g) catalyst. Catalysts propertics significantly affects product distribution and product properties. Bio-oils were mainly composed of nitrogen containing compounds. Abstract: Hydrothermal liquefaction of Ulva prolifera macroalgae (UM), an aquatic biomass, was carried out in an autoclave reactor at different temperature (270, 290 and 310 °C) and reaction holding time (10, 20 and 30 min.). The catalytic reactions of UM were carried out in the presence of three basic catalysts (KOH, NaOH and Na2 CO3 ) with the different catalyst amount. Maximum bio-oil yield for non-catalytic liquefaction was (12.0 wt%) at 290 with 10 min reaction time. In the catalytic reaction the maximum bio-oil yield (26.7 wt%) was observed with KOH (0.1 g) catalyst. The chemical components and functional groups present in the bio-oils are identified by GC–MS, FT-IR, 1 H-NMR, TGA and elemental analysis techniques. Majorly nitrogen containing compounds were found with catalytic reaction in bio-oils. The higher heating value (33.6 MJ kg −1 ) as well as the higher carbon content (64.2%) was observed in the case of catalytic liquefaction bio-oil.